Generation investigation of "eye-safe" microchip lasers pumped by 974 nm and 939 nm wavelength - Młyńczak, Jarosław; Kopczyński, Krzysztof; Mierczyk, Zygmunt (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The paper describes the results of spectroscopic and generation investigations of Concentrated and SELG glasses with different concentrations of dopants. Transmission spectra of the glasses were measured and absorption coefficients calculated. The laser generation was carried out using two different pump wavelengths of 974 nm and 939 nm in cw and quasi-cw regimes. Attempts to compare the efficiencies of pumping by these two different wavelengths and the evaluation of the optimal thickness of the active media were made.
Optica Applicata, Vol. 38, 2008, nr 4, s. 657-668
Keywords: optyka; erbium glasses; microchip lasers; "eye-safe" laser radiation